(untitled) (BRAC University Journal, 2026)
Although money demand equations have been estimated for many western countries, yet only recently many researchers have investigated the demand for money in mixed economies like Bangladesh. Co-integration technique is now a common method of estimating any money demand function. This paper empirically analyses the stability of the narrow and broad money demand functions (M1, M2, and M3) in Bangladesh for the period 1999QI-2005QIIII. To determine whether the policy framework satisfies the necessary condition for effectiveness of monetary policy, the stability of Bangladeshi M1, M2, and M3 money demand is estimated and tested by employing a recent co-integration procedure proposed by Johansen-Juselius (2001). It is shown that even though M1 and M2 monetary aggregates are co-integrated with income, interest rate and nominal effective exchange rate, application of Cumulative Sum (CUSUM) and Cumulative Sum of Square (CUSUMSQ) tests to the residuals of an error-correction model reveal that it is unstable.